2016
DOI: 10.1159/000448585
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia and Rewarming Activate a Macroglial Unfolded Protein Response Independent of Hypoxic-Ischemic Brain Injury in Neonatal Piglets

Abstract: Therapeutic hypothermia provides incomplete neuroprotection after hypoxia-ischemia (HI)-induced brain injury in neonates. We previously showed that cortical neuron and white matter apoptosis are promoted by hypothermia and early rewarming in a piglet model of HI. The unfolded protein response (UPR) may be one of the potential mediators of this cell death. Here, neonatal piglets underwent HI or sham surgery followed by 29 h of normothermia, 2 h of normothermia + 27 h of hypothermia or 18 h of hypothermia + rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Preclinical and clinical studies of neonatal brain hypoxia suggest that rewarming may cause cytotoxic injury or otherwise may be detrimental to the brain. 1619 The longer duration of low blood pressure and greater blood pressure variability during rewarming may have improved sensitivity for detecting these relationships (Fig 2). These observations may also reflect the withdrawal of hypothermia and highlight a potential role for autoregulation monitoring in determining the need for continued therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies of neonatal brain hypoxia suggest that rewarming may cause cytotoxic injury or otherwise may be detrimental to the brain. 1619 The longer duration of low blood pressure and greater blood pressure variability during rewarming may have improved sensitivity for detecting these relationships (Fig 2). These observations may also reflect the withdrawal of hypothermia and highlight a potential role for autoregulation monitoring in determining the need for continued therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies are needed to define the interactions between temperature and autoregulation in specific regions. Hypothermia and rewarming do not fully protect cortical grey matter and white matter from apoptotic cell death, [3335] and blood pressure below the optimal autoregulatory level may render these regions more vulnerable to cell death. By contrast, the neuroprotection afforded by hypothermia in the putamen [36] may delay vulnerability to sub-optimal autoregulatory function until normothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Given a recent study which indicated that the cell stress response underlies ring-stage artemisinin resistance (Zhang et al, 2017), and evidence that temperature modulations induce a similar stress response in higher eukaryotes (Lee et al, 2016; Rzechorzek et al, 2015a; Liu et al, 2013; Kim et al, 2013; Xu et al, 2011), we sought to clarify the impact of temperature variation on P. falciparum susceptibility to artemisinin in the ring stage survival assay (RSA). Unlike the methods used in previous studies, the in vitro readouts from this assay correlate well with clinical treatment outcomes (Witkowski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%